Democratic Socialism a Solution to Colonial Tourism Structures - Kennedy-Jude Providence (Caribbean Studies Students' Union, 2022)
The Caribbean's environmental diversity and tourism products have been a longstanding source of income leading many to argue that the detriments of tourism outweigh its beneficial, economic effects. However, as the COVID-19 pandemic changed the course of travel- and by extension, tourism, countries have been forced to re-evaluate travel structures, means of income and longstanding Clientelist relationships with their North American neighbours. In this commentary, I discuss the socio- economic effect of the COVID-19 pandemic on tourism- in the context of Jamaica; as well as the possibility of re-engineering Democratic Socialism for implementation in the post-pandemic environ- ment as a way to psychologically decolonize the region and alleviate the potentially lingering, devastating effects of the pandemic. Furthermore, while there are other prevalent issues that threaten tourism and have plagued the region for years including and not limited to pollution, environmen- tal degradation, climate change, crime and natural disasters, this analysis is simply intended to focus on identity, economy and the seemingly never-end- ing cycle of Western Imperialism threatening West Indian identity.